Measurement of environmentally sensitive productivity growth in Korean industries - Yeimin Chung; Almas Heshmati (Institute for the Study of Labor (IZA), 2013)
This study measures productivity growth using the Metafrontier Malmquist-Luenberger productivity growth index (MML index) method and decomposes the index. The results are compared with those obtained from the conventional Malmquist-Luenberger (ML) productivity growth index. MML has two advantages compared with the ML index. The former is able to consider undesirable output as a by-product of production which accounts for producer group heterogeneities. As a result, it enables separation and estimation of changes in the technological gap between regional and global frontier technologies. The proposed index is employed to measure productivity growth and decompose its components in 14 Korean industrial sectors during the period between 1981 and 2007. For the purpose of detailed analysis of policy effects, the study period was divided into three decades. The results show that technology innovation can be regarded as a more important factor of productivity growth, rather than efficiency change. The chemical and Petrochemical, Machinery and Transport equipment industries are treated as global innovators in the whole period. However, the result differs according to decades. It is found that the groups with higher energy efficient technology and profitability obtain a higher productivity growth rate in comparison with their low energy efficient technology industry counterparts. Policy implications of the empirical results are discussed.
Keywords: D24; C61; O31; O44; 330; CO2 emission; undesirable output; DEA; Malmquist-Luenberger productivity (ML) index; Metafrontier Malmquist-Luenberger productivity (MML) index; productivity change